C57BL/6 mice are resistant to joint degeneration induced by whole-body vibration. Issue 3 (March 2017) - Kerr, G.J.; McCann, M.R.; Branch, J.K.; Ratneswaran, A.; Pest, M.A.; Holdsworth, D.W.; Beier, F.; Dixon, S.J.; Séguin, C.A.
Summary: Objective: Whole-body vibration (WBV) platforms are commercially available devices that are used clinically to treat numerous musculoskeletal conditions based on their reported ability to increase bone mineral density and muscle strength. Despite widespread use, there is an alarming lack of understanding of the direct effects of WBV on joint health. Previous work by our lab demonstrated that repeated exposure to WBV using protocols that model those used clinically, induces intervertebral disc (IVD) degeneration and osteoarthritis-like damage in the knee of skeletally mature, male mice of a single outbred strain (CD-1). The present study examined whether exposure to WBV induces similar deleterious effects in a genetically different strain of mouse (C57BL/6). Design: Male 10-week-old C57BL/6 mice were exposed to vertical sinusoidal WBV for 30 min/day, 5 days/week, for 4 or 8 weeks using previously reported protocols (45 Hz, 0.3  g peak acceleration). Following WBV, joint tissues were examined using histological analysis and gene expression was quantified using real-time PCR (qPCR). Results: Our analyses show a lack of WBV-induced degeneration in either the knee or IVDs of C57BL/6 mice exposed to WBV for 4 or 8 weeks, in direct contrast to the WBV-induced damage previously reported by our lab in CD-1 mice. Conclusions: Together with previous studies from our group, the present study demonstrates that the effects of WBV on joint tissues vary in a strain-specific manner. These findings highlight the need to examine genetic or physiological differences that may underlie susceptibility to the deleterious effects of WBV on joint tissues.